Dynamic simulation and experimental study of a novel Al extraction method from AlN under vacuum. (September 2015) - Lu, Yong; Zhou, Yuezhen; Wu, Chunhan; Chen, Xiumin; Wang, Jiaju; Yu, Qingchun; Liu, Dachun; Yang, Bin
Abstract: AlN chlorination route, in the present work, was proposed to extract Aluminum from aluminum nitride under vacuum. Density functional theory (DFT) were implemented to study the interaction of AlCl3 molecule and AlN ( 10 1 ¯ 0 ) surface. The results of DFT indicate that chemisorbed AlCl3 adsorption configuration was observed on the clean AlN ( 10 1 ¯ 0 ) surface after structure optimization, and adsorbed AlCl molecules were generated after 1 ps dynamic simulation time. The phase and composition of condensate were examined by means of XRD and EDS. It was found that 97.76 wt% of Al metal was obtained in the experiment B (in the presence of AlCl3 ), however, no condensate was collected in the experiment A (without AlCl3 ) at 1760 K under pressure of average 60 Pa. The results show that AlN chlorination route is an alternative Al production method from aluminum nitride. Highlights: 97.76 wt% of aluminum metal was obtained by AlN chlorination route. Chlorination route was an alternative Al extraction method from AlN. Chlorination process was much more easily than thermal dissociation of AlN. The spontaneous reaction temperature was decreased under vacuum.